A Behavioral Intervention Increases Consumption of a New Biofortified Food by School Children: Evidence from a Field Experiment in Nigeria - Just, D.R.; Okello, J.J.; Gabrielyan, G.; Adekambi, S.; Kwikiriza, N.; Abidin, P.E.; Carey, E.E. (Springer, 2022)
Children's diets can have major implications for a wide range of diseases and their development outcomes. In Africa, micronutrient deficiency remains a major challenge and affects the health and development of vulnerable populations, especially children. A major effort to combat micronutrient deficiency has targeted biofortification of staple foods, with greatest potential being registered in the enrichment of, among others, sweetpotato with beta carotene-a precursor for vitamin A. However, overcoming vitamin A deficiency is made all the more complicated by children's general resistance to unfamiliar foods. We report the results of a field experiment in Nigerian schools designed to use behavioral techniques to promote consumption of an unfamiliar food: the pro-vitamin A rich orange-fleshed sweetpotato. We find that children eat more, on average, when the sweetpotato is introduced alongside behavioral nudges such as songs or association with aspirational figures. These results appear to conform to results found in a developed country context.